STUDENT PARTICIPATION IN BUILDING VILLAGES IN ENHANCING SUSTAINABLE DEVELOPMENT - SUSTAINABLE DEVELOPMENT GOALS - Danil, Mahmud; Luthfie, Muhammad (Administratie: Jurnal Administrasi Publik, 2024)
The 2023 Village Building Higher Education Program, spearheaded by LLDikti Region IV, serves as a crucial avenue for student engagement beyond the confines of the campus, particularly through the organization of Village/Thematic Real Work Lectures. Thematic KKN, a form of educational initiative, immerses students in community settings outside the campus, fostering hands-on learning experiences. This direct interaction with local communities enables the identification of opportunities and solutions, ultimately aiming to foster regional development and tackle prevalent challenges effectively. The primary objective of this endeavor is to empower students to actively contribute to the creation of an innovative village ecosystem, particularly in areas like business and entrepreneurship. Through a qualitative descriptive methodology, this study seeks to comprehensively grasp the dynamics, perceptions, and outcomes of student participation in the program. Data collection methods, including in-depth interviews and document analysis, were employed among participating students across various program facets. The research findings elucidate the diverse forms of student involvement, delineating both encountered obstacles and perceived benefits stemming from program engagement. Rooted in Max Weber's theoretical framework, this involvement spans multiple dimensions, encompassing the contribution of ideas, resources, and efforts, all directed towards achieving key program objectives, notably poverty alleviation and addressing issues such as stunting.